Working in the open: lessons from open source on building communities of educational innovation. Issue 3 (8th August 2016) - Santo, Rafi; Ching, Dixie; Peppler, Kylie; Hoadley, Christopher
Abstract : Purpose: This article makes the case that the education community can learn from professional learning and innovation practices, collectively called 'Working in the Open' (or 'Working Open'), that have roots in the Free/Open Source Software movement. These practices focus on values of transparency, collaboration and sharing within communities of experimentation. We argue that Working Open offers a compelling approach to fostering distributed educational professional ecosystems that focus on co-constructing new projects as well as best practices. Design/methodology/approach: Insights presented here are based on three sources: (1) expert perspectives on open source work practices gleaned through interviews and blog posts, (2) a qualitative case case analysis of a collaborative project enacted by a group of informal learning organizations within the Hive NYC Learning Network, a community of over 70 youth-facing organizations in New York City, as well as an overview of that community's participation structures and finally (3) knowledge-building activities and discussions held within the Hive NYC community about the topic. Analysis focused on operationalizing emic understandings of 'Working in the Open' and manifestations of these practices and supportive structures in situ and derived from this general principles to guide open work approaches. Findings: We identify five practices deemed as central to Working Open: (1) Public Storytelling and Context Setting, (2) Enabling Community Contribution, (3) Rapid Prototyping 'in the Wild', (4) Public Reflection and Documentation and, lastly, (5) Creating Remixable Work Products. We describe these practices, show how they are enacted in situ, outline ways that Hive NYC stewards promote a Working Open organizational ecosystem and conclude with recommendations for utilizing a Working Open approach. Originality/value: Drawing from the Free/Open Source Software movement, this article builds on standard practices of professional learning communities to provide an approach that focuses on pushing forward innovation and changes in practice as opposed to solely sharing reflections or observing practices.